2018
DOI: 10.1186/s12889-018-5771-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to second-hand tobacco smoke and respiratory symptoms in non-smoking adults: cross-sectional data from the general population of Telemark, Norway

Abstract: BackgroundIn Norway, data on the association between second-hand tobacco smoke (SHS) exposure at home and respiratory symptoms in adults are limited.MethodsWe assessed the association between self-reported exposure to SHS and the prevalence of respiratory symptoms among never-smokers aged 16 to 50 years from the general population who were included in a cross-sectional population-based study in Telemark County, Norway. Logistic regression analysis was used to estimate the odds ratios of symptoms among 8850 nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The study also found that increased exposure to second-hand smoke was associated with a reduction in lung functions in ever-smokers and never or non-smokers, with ever-smokers showing strong association because of frequent and high exposure to toxic substances of smoke, which causes lung inflammation that triggers the development of lung cancer. 12 Similar findings were supported in a recent study among older Amish in the United States, which showed that high exposure to passive or second-hand smoke was associated with poor lung function, which is characterized by lower forced respiratory volume. 13 Despite several studies indicate a strong association between passive smoking and lung cancer, very few studies show no link between the two.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The study also found that increased exposure to second-hand smoke was associated with a reduction in lung functions in ever-smokers and never or non-smokers, with ever-smokers showing strong association because of frequent and high exposure to toxic substances of smoke, which causes lung inflammation that triggers the development of lung cancer. 12 Similar findings were supported in a recent study among older Amish in the United States, which showed that high exposure to passive or second-hand smoke was associated with poor lung function, which is characterized by lower forced respiratory volume. 13 Despite several studies indicate a strong association between passive smoking and lung cancer, very few studies show no link between the two.…”
Section: Discussionsupporting
confidence: 76%
“…The study assessed the association of second-hand smoke exposure and lung cancer among non-smokers aged between 16 years and 50 years in Telemark County in Norway. 12 In their study, the researchers found that exposure to second-hand or passive smoke in non-smokers results in respiratory effects, including nocturnal dyspnoea and productive cough, which are the key predictors of lung cancer. The study indicated that frequent exposure to second-hand smoke increases the prevalence of chronic cough due to the chronic inflammation in the lungs, which triggers the pathogenesis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not ask for or analyze the effects of second hand tobacco smoke exposure especially at home which may also be an important factor in respiratory symptoms. [22] Third, spirometry was not used to evaluate pulmonary functions. And lastly, we did not record the period of non-smoking among former-smoker or the number of cigarettes smoked per day in current-smokers which may also have some effects on respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…One in five respondents indicated the presence of ETS in their homes. Exposure to active and passive smoking is associated with increased risk of respiratory infections [41,42]. In those households in which smokers were present, respiratory infections may have been exacerbated by smoke inhalation, either active or passive.…”
Section: Discussionmentioning
confidence: 99%